Association of Hospital Surgical Volume With Survival in Early-Stage Cervical Cancer Treated With Radical Hysterectomy. Issue 1 (30th January 2023) - Bizzarri, Nicolò; Dostálek, Lukáš; van Lonkhuijzen, Luc R. C. W.; Giannarelli, Diana; Lopez, Aldo; Falconer, Henrik; Querleu, Denis; Ayhan, Ali; Kim, Sarah H.; Ortiz, David Isla; Klat, Jaroslav; Landoni, Fabio; et al.
Abstract : Women with early-stage cervical cancer treated with primary radical hysterectomy had improved disease-free survival when treated in hospitals with a higher surgical volume. Abstract : OBJECTIVE: To evaluate the association of number of radical hysterectomies performed per year in each center with disease-free survival and overall survival. METHODS: We conducted an international, multicenter, retrospective study of patients previously included in the Surveillance in Cervical Cancer collaborative studies. Individuals with International Federation of Gynecology and Obstetrics (FIGO) 2009 stage IB1–IIA1 cervical cancer who underwent radical hysterectomy and had negative lymph nodes at final histology were included. Patients were treated at referral centers for gynecologic oncology according to updated national and international guidelines. Optimal cutoffs for surgical volume were identified using an unadjusted Cox proportional hazard model, with disease-free survival as the outcome and defined as the value that minimizes the P -value of the split in groups in terms of disease-free survival. Propensity score matching was used to create statistically similar cohorts at baseline. RESULTS: A total of 2, 157 patients were initially included. The two most significant cutoffs for surgical volume were identified at seven and 17 surgical procedures, dividing the entire cohort into low-volume, middle-volume, and high-volume centers. After propensity score matching, 1, 238 patients were analyzed—619 (50.0%) in the high-volume group, 523 (42.2%) in the middle-volume group, and 96 (7.8%) in the low-volume group. Patients who underwent surgery in higher-volume institutions had progressively better 5-year disease-free survival than those who underwent surgery in lower-volume centers (92.3% vs 88.9% vs 83.8%, P =.029). No difference was noted in 5-year overall survival (95.9% vs 97.2% vs 95.2%, P =.70). Cox multivariable regression analysis showed that FIGO stage greater than IB1, presence of lymphovascular space invasion, grade greater than 1, tumor diameter greater than 20 mm, minimally invasive surgical approach, nonsquamous cell carcinoma histology, and lower-volume centers represented independent risk factors for recurrence. CONCLUSION: Surgical volume of centers represented an independent prognostic factor affecting disease-free survival. Increasing number of radical hysterectomies performed in each center every year was associated with improved disease-free survival.